Polyolefin Composition Comprising Polypropylene Homopolymer and Recycled Plastic Materials
By using polypropylene homogenomes, composite polyester materials and other additives in polyester materials, the emission, odor and atomization problems when replacing virgin polyester materials in automotive applications are solved, and the dual improvement of the thermomechanical and environmental performance of polyester materials is achieved.
Patent Information
- Application Number
- JP2024501569
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2021-07-13
- Filing Date
- 2022-07-06
- Publication Date
- 2025-04-03
- Estimated Expiration
- 2042-07-06
AI Technical Summary
The prior art is difficult to replace virgin polyester materials in automotive applications, especially to improve emissions, odor and atomization problems while maintaining the thermomechanical properties of the polyester materials.
The polyester material is formed by using 20-30% polypropylene homopolymer and 10-45% composite polyester material from waste plastic, combined with 7-15% heterophase polypropylene copolymer, 1-4% elastomer, 15-25% glass fiber and 0.5-2.5% coupling agent and other additives.
The emission, odor and atomization properties of polyester materials are significantly improved, while maintaining the thermomechanical properties of polyester materials, meeting the needs of automotive applications.
Smart Images

Figure 0007656772000001 
Figure 0007656772000002 
Figure 0007656772000003
Abstract
Description
[Technical field]
[0001] The present invention relates to a polyolefin composition comprising at least one polypropylene homopolymer and recycled plastic material, as well as to articles comprising said polyolefin composition and to a process for preparing such a polyolefin composition. [Background technology]
[0002] Polyolefins, particularly polyethylene and polypropylene, are increasingly being consumed in large quantities in a wide range of applications including packaging for food and other commodities, textiles, automotive parts, and a wide variety of manufactured goods. Considering the large amount of waste that is recovered compared to the amount that is recycled back into the stream, it can be seen that there remains a great deal of potential for intelligent reuse of plastic waste streams and mechanical recycling of plastic waste.
[0003] Generally, the recycled polypropylene volumes on the market are a mixture of both polypropylene (PP) and polyethylene (PE), which is especially true for post-consumer waste streams. Furthermore, commercial recyclates from post-consumer waste sources are traditionally cross-contaminated with non-polyolefin materials such as polyethylene terephthalate, polyamide, polystyrene, or non-polymeric substances such as wood, paper, glass, or aluminum. These cross-contaminations dramatically limit the end-use of the recycle stream such that no beneficial end-use remains. In particular, polyolefin recycle materials from post-consumer waste streams are a mixture of PE and PP. The better the quality of the recycle, the less available and the higher the price.
[0004] Customers looking for recycled products demand similar performance to virgin products, and this is also the case for reinforced glass fiber compounds for structural products. The quality issues of recycled compared to virgin can be overcome to some extent by reinforcing the recycled product, where the reinforcing particles physically bond the different domains (PP and PE).
[0005] Glass fiber (GF)-reinforced recycled mixed plastics are also being investigated, for example recycled PP or PP / PE blends are reinforced with GF or hybrid GF with other fillers.
[0006] EP2845876B1 describes a composition containing two or more types of resin and glass fiber, the composition including a resin mixture containing waste polyethylene (PE) and waste polypropylene (PP); long glass fiber having a length of 10 mm or more; and a rubber-based resin, the composition including, per 100 parts by weight of the resin mixture, 3 to 30 parts by weight of the long glass fiber, 10 to 50 parts by weight of the rubber-based resin, and 10 to 35 parts by weight of LDPE.
[0007] Thus, there are examples of reinforced recycled products that simultaneously have good tensile modulus and impact strength.
[0008] Automotive interior components such as dashboards, door coverings, trim, etc. are commonly made from polymers, particularly filled propylene-based resins, which are widely used for these applications due to their excellent chemical and heat resistance.
[0009] Furthermore, in recent years, low emissions, low amounts of volatile organic compounds, low fogging, reduced odor, and improved sensory properties of polymeric materials have become further important challenges in automotive applications, often resulting in the development of the 25 term EFO (Emission, Fog, Odour). Volatile organic compounds (VOC) are defined as the emission of very light to light alkanes with chain length C4-C20, measured according to VDA 278:2002. FOG values are defined as the emission of additives, alkanes and oligomers with chain length C16-C32, also measured according to VDA 278:2002.
[0010] Some of the emitted volatile substances can form a precipitate called "fogging" on the windshield, which adversely affects visibility and therefore the safety of the driver and passengers. The term fogging refers to the emission of additives and aliphatic oligomers with a chain length of C30 or more. It means that the gases emitted from the individual materials precipitate and form an oily film on the windshield. These condensable components can be measured by gravimetric fogging tests, which measure the increase in weight due to condensation. Since the fogging value involves substances different from the VOCs and FOGs, the fogging value cannot be concluded from the VOCs and FOGs of the material. Furthermore, fogging is often increased by additives added to achieve the required mechanical properties, so reducing the fogging value is a major challenge in the polymer industry.
[0011] This fogging issue is exacerbated when virgin polymers are replaced with polymer recyclates: standard recycled materials suffer from bad odors and poor performance in emissions, including high residues during exposure, as reflected in the fogging test results.
[0012] Therefore, when attempting to replace at least a portion of virgin polymers with recycled materials in automotive applications, not only the thermomechanical properties of the polymer composition must be addressed, but also the emissions properties. [Prior art documents] [Patent documents]
[0013] [Patent Document 1] European Patent No. 2845876 Summary of the Invention [Problem to be solved by the invention]
[0014] It was therefore an object of the present invention to provide a polyolefin composition, in particular for automotive applications, in which at least a portion of the virgin polyolefin is replaced with polyolefin material recovered from waste plastic materials, at least maintaining the thermomechanical properties of the polyolefin composition while improving the emission, odor and fogging properties of the polyolefin composition. [Means for solving the problem]
[0015] The purpose of this is to a) 20 to 30 wt. % (based on the total weight of the polyolefin composition) of at least one polypropylene homopolymer; b) a blend of recycled plastic materials comprising 10-45% by weight (based on the total weight of the polyolefin composition) of polypropylene and polyethylene in a ratio of 3:7 to 49.5:1, recovered from waste plastic materials originating from post-consumer and / or post-industrial waste; c) 7 to 15 wt. % (based on the total weight of the polyolefin composition) of at least one heterophasic polypropylene copolymer; d) 1 to 4 weight percent (based on the total weight of the polyolefin composition) of at least one elastomer; e) 15 to 25 wt. % (based on the total weight of the polyolefin composition) of at least one glass fiber; and f) 0.5 to 2.5 wt. % (based on the total weight of the polyolefin composition) of at least one coupling agent and, optionally, further additives; Including, A polyolefin composition, wherein the total of all components is always added to be 100% by weight, The polyolefin composition is characterized by: - Solved by providing a fogging value of 0.5 to 2.00 (measured gravimetrically according to ISO 75201, Method B). Effect of the Invention
[0016] Thus, a polyolefin composition is provided that includes recycled plastic material, virgin polypropylene polymer, heterophasic propylene copolymer, elastomer, glass fiber to provide mechanical strength, and a suitable coupling agent, which combination provides significant improvements in fogging. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0017] It is to be understood that the polyolefin composition is free of talc (except for the amount present in the recyclate), rubber, and essentially free of peroxides, preferably having a peroxide content of less than 0.5 wt.% based on the total weight of the polyolefin composition.
[0018] For the purposes of this specification and the claims that follow, the term "recycled" is used to indicate that materials are recovered from post-consumer and / or post-industrial waste, i.e., post-consumer waste refers to materials that have completed at least their first use cycle (or life cycle), i.e., have already fulfilled their first purpose and passed through the hands of the consumer, while post-industrial waste refers to manufacturing scrap that usually does not reach the consumer.
[0019] As further described below, typical other components from the original use are thermoplastic polymers such as polystyrene and PA6, talc, chalk, ink, wood, paper, limonene and fatty acids. The polystyrene (PS) and polyamide 6 (PA6) content in the recycled polymers can be measured by Fourier transform infrared spectroscopy (FTIR), and the talc, chalk, wood and paper content can be measured by thermogravimetric analysis (TGA). It should be understood that the small amount of talc present in the recycled plastic material is not included in the amount of particulate material subsequently added to the polyolefin composition.
[0020] The term "virgin" refers to a newly manufactured material and / or object that has not been recycled, prior to its first use. If the origin of the polymer is not explicitly stated, the polymer is a "virgin" polymer.
[0021] The fogging value of the polyolefin composition (measured gravimetrically according to ISO 75201, method B) may be in the range of 0.75 to 1.8, preferably 0.9 to 1.7, more preferably 1.30 to 1.60, even more preferably 1.30 to 1.57, even more preferably 1.3 to 1.5, and most preferably 1.40 to 1.50.
[0022] In one embodiment, the polyolefin composition is further characterized by a melt flow rate MFR2 (230°C, 2.16 kg, measured according to ISO 1133) of at least 7 g / 10 min, preferably in the range of 8-15 g / 10 min, preferably 9-15 g / 10 min, more preferably 9-13 g / 10 min. In one embodiment, the polyolefin composition may have a fogging value of 1.30 to 1.40 and a MFR2 of 9 to 15 g / 10 min, for example, 12 to 15 g / min.
[0023] In another embodiment, the polyolefin composition is characterized by a tensile modulus (ISO 527-2) of at least 3.5 GPa, preferably at least 4 GPa, more preferably at least 4.5 GPa, especially in the range of 4 to 5 GPa, more especially in the range of 4.5 to 5 GPa.
[0024] In yet another embodiment, the polyolefin composition has a flexural modulus (ISO 178) of at least 3.5 GPa, preferably at least 4 GPa, more preferably at least 4.5 GPa, especially in the range of 4 to 5 GPa, more especially in the range of 4.5 to 5 GPa.
[0025] In a further embodiment, the polyolefin composition has a viscosity of at least 5.0 kJ / m 2 , preferably at least 6 kJ / m 2 , more preferably at least 6.5 kJ / m 2 , more preferably at least 7.0 kJ / m 2 , especially 6.0~9.0kJ / m 2 In particular, in the range of 6.5 to 8.0 kJ / m 2 In particular, in the range of 7.0 to 8.0 kJ / m 2 It has an impact strength in the range of (ISO179-1, Charpy 1eA +23℃).
[0026] The polypropylene homopolymer used as the virgin polymer in the present polyolefin composition is selected from the group comprising: at least one polypropylene homopolymer (PPH-1) having a melt flow rate MFR2 (measured according to ISO 1133 at 230°C, 2.16 kg) ranging from 10 to 30 g / 10 min, preferably from 15 to 25 g / 10 min, more preferably from 18 to 22 g / 10 min; at least one polypropylene homopolymer (PPH-2) having a melt flow rate MFR2 (230°C, 2.16 kg, measured according to ISO 1133) ranging from 60 to 100 g / 10 min, preferably from 70 to 80 g / 10 min, more preferably from 73 to 77 g / 10 min; at least one polypropylene homopolymer (PPH-3) having a melt flow rate MFR2 (230°C, 2.16 kg, measured according to ISO 1133) ranging from 100 to 150 g / 10 min, preferably from 100 to 130 g / 10 min, more preferably from 122 to 128 g / 10 min; at least one polypropylene homopolymer (PPH-4) having a melt flow rate MFR2 (230°C, 2.16 kg, measured according to ISO 1133) ranging from 50 to 100 g / 10 min, preferably from 60 to 90 g / 10 min, more preferably from 70 to 80 g / 10 min.
[0027] Polypropylene Virgin Polymer The properties and characteristics of the different polypropylene homopolymers that may be used in the polyolefin composition are described below.
[0028] Polypropylene homopolymer (PPH-1) The at least one polypropylene homopolymer (PPH-1) has a melt flow rate MFR2 (230°C, 2.16 kg, measured according to ISO 1133) in the range of 10 to 30 g / 10 min, preferably 15 to 25 g / 10 min, preferably 20 g / 10 min; and a stiffness higher than 1800 MPa.
[0029] The polypropylene homopolymer (PPH-1) consists essentially of propylene units, i.e., 99.7% or more by weight, and even more preferably at least 99.8% by weight, based on the weight of the propylene homopolymer (PPH-1). In a preferred embodiment, only propylene units are detectable in the propylene homopolymer (PPH-1).
[0030] It is understood that the polypropylene homopolymer (PPH-1) is characterized by a low amount of xylene cold soluble (XCS) fraction. The polypropylene homopolymer (PPH-1) may have an amount of xylene cold soluble (XCS) fraction of 4.0% or less by weight, preferably 3.0% or less by weight, more preferably 2.5% or less by weight, for example, in the range of 0.1 to 4.0% by weight, preferably 0.1 to 3.0% by weight, more preferably 0.1 to 2.5% by weight, based on the weight of the polypropylene homopolymer (PPH-1).
[0031] The polypropylene homopolymer (PPH-1) may have a deflection temperature under load (HDT), measured according to ISO 75-2, of at least 90°C, preferably at least 100°C, more preferably at least 115°C, for example in the range of 90 to 160°C, preferably 100 to 150°C, more preferably 115 to 130°C.
[0032] Polypropylene homopolymer (PPH-1) has a thermal conductivity of at least 1.0 kJ / m 2 , preferably at least 2.0 kJ / m 2 , for example, 1.0 to 10 kJ / m 2 in the range of 2.0 to 5.0 kJ / m 2 In the range of, for example, 2.5 kJ / m 2 The polypropylene homopolymer (PPH-1) may have a Charpy impact strength, measured according to ISO 179-1eA:2000 at 23° C. of at least 500 MPa, preferably at least 1500 MPa, for example in the range 500-3500 MPa, preferably in the range 1500-2500 MPa, for example 2000 MPa.
[0033] The polypropylene homopolymer (PPH-1) may contain a nucleating agent, which is preferably a polymeric nucleating agent, more preferably an α-nucleating agent, such as a polymeric α-nucleating agent. The content of the α-nucleating agent in the polypropylene homopolymer (PPH-1) is preferably 5.0% by weight or less. In a preferred embodiment, the polypropylene homopolymer (PPH-1) contains 3000 ppm or less of the α-nucleating agent, more preferably 1 to 2000 ppm.
[0034] Polypropylene homopolymer (PPH-1) is known in the art and is commercially available, for example, from Borealis AG.
[0035] Polypropylene homopolymer (PPH-2): The at least one polypropylene homopolymer (PPH-2) has a melt flow rate MFR2 (measured according to ISO 1133 at 230° C., 2.16 kg) in the range of 60 to 100 g / 10 min, preferably in the range of 70 to 80 g / 10 min, more preferably 75 g / 10 min; and a stiffness higher than 1300 MPa.
[0036] The polypropylene homopolymer (PPH-2) consists essentially of propylene units, i.e., 99.7% or more by weight, more preferably at least 99.8% by weight, based on the weight of the polypropylene homopolymer (PPH-2). In a preferred embodiment, only propylene units are detectable in the propylene homopolymer (PPH-2).
[0037] It is understood that the polypropylene homopolymer (PPH-2) is characterized by a low amount of cold xylene soluble (XCS) fraction. The polypropylene homopolymer (PPH-2) may have an amount of cold xylene soluble (XCS) fraction of 4.0 wt% or less, preferably 3.5 wt% or less, for example, in the range of 0.1 to 4.0 wt%, preferably in the range of 0.1 to 3.5 wt%, based on the weight of the polypropylene homopolymer (PPH-2).
[0038] The polypropylene homopolymer (PPH-2) may have a deflection temperature under load (HDT), measured according to ISO 75-2, of at least 50°C, preferably at least 60°C, more preferably at least 75°C, for example in the range of 50 to 120°C, preferably in the range of 60 to 100°C, more preferably in the range of 75 to 90°C.
[0039] Polypropylene homopolymer (PPH-2) has a thermal conductivity of at least 0.5 kJ / m 2 , preferably at least 0.7 kJ / m 2 , for example 0.5 to 1.5 kJ / m 2 in the range of 0.7 to 1.3 kJ / m 2 range, e.g. 1.0 kJ / m 2 The polypropylene homopolymer (PPH-2) may have a flexural modulus, measured according to ISO 178, of at least 500 MPa, preferably at least 1000 MPa, for example in the range of 500 to 2500 MPa, preferably in the range of 1000 to 2000 MPa, for example 1500 MPa.
[0040] It is understood that when the polypropylene homopolymer (PPH-2) comprises an α-nucleating agent, the polypropylene homopolymer (PPH-2) may comprise the α-nucleating agent in an amount of up to 5.0 wt. %, preferably up to 3000 ppm, for example in the range of 1 to 2000 ppm, based on the weight of the polypropylene homopolymer (PPH-3). However, in a preferred embodiment, the polypropylene homopolymer (PPH-2) does not comprise a nucleating agent, i.e., the polypropylene homopolymer (PPH-2) is not nucleated.
[0041] Polypropylene homopolymer (PPH-2) is known in the art and is commercially available, for example, from Borealis AG.
[0042] Polypropylene homopolymer (PPH-3) : The at least one polypropylene homopolymer (PPH-3) has a melt flow rate MFR2 (230°C, 2.16 kg, measured according to ISO 1133) in the range of 100 to 150 g / 10 min, preferably 110 to 130 g / 10 min, more preferably 125 g / 10 min.
[0043] Polypropylene homopolymer (PPH-3) has a thermal conductivity of at least 0.5 kJ / m 2 , preferably at least 0.7 kJ / m 2 , for example 0.5 to 1.5 kJ / m 2 in the range of 0.7 to 1.3 kJ / m 2 in the range of, for example, 1.0 kJ / m 2 The polypropylene homopolymer (PPH-3) may have a Charpy impact strength (NIS) measured according to ISO 179-1eA:2000 at 23° C. of at least 500 MPa, preferably at least 1000 MPa, for example in the range of 500 to 2500 MPa, preferably in the range of 1000 to 2000 MPa, for example 1550 MPa.
[0044] Polypropylene homopolymer (PPH-3) is known in the art and is commercially available, for example, from Borealis AG.
[0045] Polypropylene homopolymer (PPH-4): The at least one polypropylene homopolymer (PPH-4) has a melt flow rate MFR2 (230°C, 2.16 kg, measured according to ISO 1133) in the range of 50 to 100 g / 10 min, preferably 60 to 90 g / 10 min, more preferably 70 to 80 g / 10 min.
[0046] The polypropylene homopolymer (PPH-4) may have a flexural modulus, measured according to ISO 178, of at least 500 MPa, preferably at least 1000 MPa, for example in the range of 500-2500 MPa, preferably in the range of 1000-2000 MPa, for example 1400-1500 MPa.
[0047] Polypropylene is 13 It has 0.01 to 1.2 mol %, preferably 0.4 to 0.85 mol %, and more preferably 0.45 to 0.8 mol % of 2,1 and 3,1 regio-defects as measured by C NMR.
[0048] Regiodefects in propylene polymers can be of three different types, namely 2,1-erythro (2,le), 2,1-threo (2,It) and 3,1 defects. A detailed description of the structure and formation mechanism of regiodefects in polypropylene is given in Chemical Reviews 2000, 100(4), pp. 1316-1327. These defects, as detailed below, 13 It is measured using C NMR.
[0049] The term "2,1 regio-defect" as used herein is defined as the sum of 2,1-erythro regio-defect and 2,1-threo regio-defect.
[0050] It is also possible to use a mixture of at least two or more polypropylene homopolymers. In the case of two polypropylene homopolymers, the amount of each polypropylene is 20 to 30% by weight in total, for example, 10 to 15% by weight, preferably 12 to 13% by weight of the first polypropylene homopolymer and 10 to 15% by weight, preferably 12 to 13% by weight of the second polypropylene homopolymer.
[0051] Recycled Material Blend The polyolefin composition may comprise 20-40% by weight, preferably 30-40% by weight (based on the total weight of the polyolefin composition) of a blend of recycled plastic materials comprising polypropylene and polyethylene having a melt flow rate MFR2 (230°C, 2.16 kg, measured according to ISO 1133) in the range of 5-100 g / 10 min, preferably 10-80 g / 10 min, more preferably 15-50 g / 10 min.
[0052] The blend is obtained from recycled waste streams. The blend can be either recycled post-consumer or post-industrial waste, for example from the automotive industry, or a combination of both. It is particularly preferred that the blend consists of recycled post-consumer and / or post-industrial waste.
[0053] In one embodiment, the blend (A) may be a polypropylene (PP)-rich material of recycled plastic materials, which contains significantly more polypropylene than polyethylene. Recycled waste streams rich in polypropylene can be obtained, for example, from the automotive industry, in particular some automotive parts such as bumpers, which are a source of fairly pure polypropylene material in the recycling stream or can be obtained by intensified sorting. PP-rich recyclates can also be obtained from appropriately sorted yellow bag feedstocks. PP-rich materials can be obtained by selective processing, degassing and filtration, and / or by separation according to type and color, such as NIR or Raman sorting and VIS sorting. It can be obtained from domestic waste streams (i.e., it is a product of domestic recycling), such as, for example, the "yellow bag" recycling systems organized under the "Green Dot" organization operating in some regions of Germany.
[0054] Preferably, the polypropylene-rich recycled material is obtained from recycled waste by means of plastic recycling processes known in the art. Such PP-rich recycled products are commercially available, for example, from Corepla (Italian Consortium for the Collection, Recovery and Recycling of Packaging Plastic Waste), Resource Plastics Corp. (Brampton, ON), Kruschitz GmbH, Plastics and Recycling (AT), Vogt Plastik GmbH (DE), Mtm Plastics GmbH (DE), etc. Exhaustive examples of polypropylene-rich recycled materials include Dipolen® PP, Purpolen® PP (mtm Plastics GmbH), MOPRYLENE PC B-420 White, MOPRYLENE PC B 440 Light Jazz (Morssinkhof Plastics NL), SYSTALEN PP-C24000, Systalen PP-C44000, Systalen PP-C14901, Systalen PP-C17900, Systalen PP-C2400, Systalen 13704 GR 015, Systalen 13404 GR 014, Systalen PP-C14900 GR000 (Der Grune Punkt DE), Vision (Veolia) PPC BC 2006 HS or PP MONO.
[0055] It is believed that the present invention may be applicable to a wide range of recycled polypropylene materials or materials or compositions with a high recycled polypropylene content. The polypropylene rich recycled material may be in the form of granules.
[0056] As mentioned above, the polyolefin composition according to the present invention comprises a polymer blend comprising a1) polypropylene and a2) polyethylene as a blend; wherein the weight ratio of a1) to a2) is 3:7 to 49.5:1; and the polymer blend is a recycled material.
[0057] A further preferred embodiment of the present invention provides that the ratio of polypropylene a1) to polyethylene a2) is from 7:1 to 40:1, preferably from 10:1 to 30:1.
[0058] According to one embodiment, the blend of recycled plastic materials comprises a relative amount of propylene derived units of greater than 50 wt.%, preferably greater than 53 wt.%, more preferably greater than 60 wt.%, more preferably greater than 70 wt.%, more preferably greater than 75 wt.%, more preferably greater than 80 wt.%, even more preferably greater than 90 wt.%, and even more preferably greater than 95 wt.%, based on the total weight of the composition of the blend.
[0059] A further preferred embodiment of the present invention provides that the content of polypropylene a1) in the blend is in the range of 75-99 wt.%, preferably in the range of 83-95 wt.%, based on the total weight of blend A). The content of polypropylene a1) in the blend can be determined by FTIR spectroscopy, as described in the experimental section. More preferably, component a1) comprises more than 95 wt.%, preferably 96-99.9 wt.%, of isotactic polypropylene, most preferably consisting of isotactic polypropylene.
[0060] Further, the blend may have a relative amount of units derived from ethylene of less than 47% by weight, more preferably less than 40% by weight, more preferably less than 30% by weight, more preferably less than 20% by weight, and most preferably less than 10% by weight. Typically, the relative amount of units derived from ethylene is 5% by weight or more based on the total weight blend. It is understood that the ethylene present is preferably ethylene derived from polyethylene and ethylene-containing copolymers.
[0061] In another preferred embodiment of the invention, the content of polyethylene a2) in the blend is in the range of 1 to 25% by weight, preferably in the range of 5 to 20% by weight, more preferably in the range of 7 to 17% by weight, based on the total weight of blend A). The content of polyethylene a2) in the blend can be determined by Crystex as described in the experimental section. More preferably, component a2) consists of polyethylene and an ethylene-containing copolymer.
[0062] 13 The C2(SF) content of the soluble fraction of the recycle blend, determined by quantitative FT-IR spectroscopy calibrated by C-NMR spectroscopy, is in the range of 25-40 wt%, preferably 27-35 wt%, and more preferably 29-34 wt%.
[0063] 13 The C2 (CF) content of the crystalline fraction of the recycle blend, determined by quantitative FT-IR spectroscopy calibrated by C-NMR spectroscopy, is in the range of 4-20 wt%, preferably 5-15 wt%, and more preferably 6-10 wt%.
[0064] The polyethylene fraction of the recycled material may include recycled high density polyethylene (rHDPE), recycled medium density polyethylene (rMDPE), recycled low density polyethylene (rLDPE), linear low density polyethylene (LLDPE) and mixtures thereof. In a particular embodiment, the recycled material has a density of 0.8 g / cm 3 More than 0.9 g / cm 3 More than 0.91 g / cm 3 and n is 0.01 to 0.05. The polyethylene is a high density polyethylene having an average density of greater than 0.01 to 0.05.
[0065] The polyethylene fraction of the recycled material may also contain plastomers, which are polymeric materials that combine rubber-like properties with the processability of plastics. Important plastomers are ethylene-alpha olefin copolymers.
[0066] The ethylene-based plastomer is preferably a copolymer of ethylene and a C4-C8 α-olefin. Suitable C4-C8 α-olefins include 1-butene, 1-hexene and 1-octene, preferably 1-butene or 1-octene, more preferably 1-octene. Preferably, copolymers of ethylene and 1-octene are used. Such ethylene-based plastomers are commercially available, for example, from Borealis AG (AT) under the trade name Queo, from DOW Chemical Corp (USA) under the trade name Engage or Affinity, or from Mitsui under the trade name Tafmer. Alternatively, the ethylene-based plastomers can be prepared by known processes in the presence of suitable catalysts, such as vanadium oxide catalysts or single-site catalysts, such as metallocene catalysts or constrained geometry catalysts, known to those skilled in the art, in one- or two-stage polymerization processes including solution polymerization, slurry polymerization, gas phase polymerization or combinations thereof. The ethylene-based plastomers may already be contained in the post-consumer and / or industrial waste used to produce the recycled mixture. Alternatively, the ethylene-based plastomers can be added to the post-consumer and / or industrial waste during the recycling process of waste plastics from which the recycled blend is produced.
[0067] In another preferred embodiment of the present invention, it is provided that the recycled blend comprises less than 5 wt.-%, preferably less than 3 wt.-%, more preferably between 0.01 and 2 wt.-%, more preferably less than 4.0 wt.-% PA6 and less than 5 wt.-% polystyrene, based on the total weight of the recycled blend of thermoplastic polymers different from a1) and a2), and even more preferably the blend comprises 0.5 to 3 wt.-% polystyrene.
[0068] In yet another preferred embodiment of the present invention, the recycled blend comprises less than 5 wt. %, preferably less than 4 wt. %, more preferably 0.01-4 wt. %, based on the total weight of the recycled blend, of talc.
[0069] In another preferred embodiment of the invention, the recycle blend comprises less than 4 wt.%, preferably less than 3 wt.%, more preferably 0.01-2 wt.%, based on the total weight of the recycle blend of chalk.
[0070] In another preferred embodiment of the invention, the recycled blend comprises less than 1% by weight, preferably less than 0.5% by weight, more preferably 0.01-1% by weight, based on the total weight of the recycled blend of paper.
[0071] In yet another preferred embodiment of the invention, the recycled blend is provided to contain less than 1% by weight, preferably less than 0.5% by weight, more preferably 0.01-1% by weight, based on the total weight of the recycled blend of wood.
[0072] In another preferred embodiment of the invention, the recycle blend contains less than 1 wt. %, preferably less than 0.5 wt. %, more preferably 0.01-1 wt. %, based on the total weight of the recycle blend of metals.
[0073] According to the present invention, the recycled blend has a limonene content, determined using solid phase microextraction (HS-SPME-GC-MS), of 0.1 ppm to 100 ppm, more preferably 1 ppm to 50 ppm, and most preferably 2 ppm to 35 ppm. Limonene is traditionally found in recycled polyolefin materials, originating from packaging applications in the fields of cosmetics, detergents, shampoos and similar products. Thus, the recycled blend will contain limonene if the recycled blend contains materials originating from such types of household waste streams.
[0074] The fatty acid content is yet another indicator of the recycled origin of the recycled blend. However, in some cases, due to certain treatments in the recycling process, the fatty acid content may be below the detection limit. According to the present invention, the recycled blend has a fatty acid content, determined using solid phase microextraction (HS-SPME-GC-MS), of preferably 1 ppm to 200 ppm, preferably 1 ppm to 150 ppm, more preferably 2 ppm to 100 ppm, and most preferably 3 ppm to 80 ppm.
[0075] In a preferred embodiment, the recycled blend (i) contains less than 5 wt.%, preferably less than 1.5 wt.%, polystyrene, and / or (ii) contains less than 3.5 wt.%, preferably less than 1 wt.%, talc, and / or (iii) contains less than 1.0 wt.%, preferably less than 0.5 wt.%, polyamide.
[0076] The recycled blend may contain organic and / or inorganic fillers and / or additives in an amount of up to 10% by weight, preferably up to 3% by weight, based on the weight of the blend.
[0077] Thus, in one embodiment of the polyolefin composition, the blend (A) of recycled plastic materials comprises: A-1) Polypropylene content of 50 to 99% by weight; A-2) polyethylene content of 1 to 40% by weight; A-3) 0 to 5.0% by weight of polystyrene and / or copolymers such as ABS, A-4) 0 to 3.0% by weight of a stabilizer, A-5) 0 to 4.0% by weight of polyamide-6, A-6) 0 to 3.0% by weight of talc, A-7) 0 to 3.0% by weight of chalk, A-8) 0 to 1.0% by weight of paper, A-9) 0 to 1.0% by weight of wood, A-10) 0 to 0.5% by weight of metal, A-11) Limonene, from 0.1 ppm to 100 ppm, as determined using solid phase microextraction (HS-SPME-GC-MS), and A-12) Total fatty acid content, 0-200 ppm, determined using solid phase microextraction (HS-SPME-GC-MS) where all amounts are given relative to the total weight of the recycle blend.
[0078] As noted above, the recycled blend may include one or more additional components selected from the following: Based on total weight of recycled blend A-4) 3.0% by weight or less of a stabilizer, preferably 2.0% by weight or less of a stabilizer, A-5) 4.0% by weight or less of polyamide-6, preferably 2.0% by weight or less of polyamide-6; A-6) 3.0% by weight or less of talc, preferably 1.0% by weight or less of talc; A-7) 3.0% by weight or less of chalk, preferably 1.0% by weight or less of chalk; A-8) 1.0% by weight or less of paper, preferably 0.5% by weight or less of paper; A-9) 1.0% by weight or less of wood, preferably 0.5% by weight or less of wood, and A-10) 0.5% by weight or less of metal, preferably 0.1% by weight or less of metal.
[0079] In one embodiment, the blend of recycled plastic materials may have a melt flow rate (ISO 1133, 2.16 kg, 230° C.) in the range of 4 to 20 g / 10 min, preferably 5 to 15 g / 10 min, more preferably 6 to 12 g / 10 min.
[0080] In another embodiment, the blend of recycled plastic materials may have a melt flow rate MFR2 (ISO 1133, 230° C., 2.16 kg) in the range of 16-50 g / 10 min, preferably 18-22 g / 10 min.
[0081] In yet another embodiment, the blend of recycled plastic materials may have a melt flow rate MFR2 (ISO 1133, 230°C, 2.16 kg) in the range of 5-100g / 10min, preferably 10-85g / 10min, preferably 15-50g / 10min, more preferably 20-50g / 10min or 20-30g / 10min or 20-25g / 10min. In one embodiment, the blend has an MFR2 of 80-90g / 10min. In another embodiment, the blend has an MFR2 of 20-30g / 10min.
[0082] In a further preferred embodiment of the present invention, the Charpy notched impact strength measured according to ISO 179-1eA at 23° C. is 3.0 kJ / m 2 or more, preferably 4.0 to 8.0 kJ / m 2 More preferably, it is in the range of 5.0 to 6.0 kJ / m 2 The range is.
[0083] In a further preferred embodiment of the present invention, it is specified that the tensile modulus of the recycled blend A, measured according to ISO 527-2, is in the range of 800 to 1500 MPa, preferably in the range of 1100 to 1400 MPa.
[0084] Next, the properties of the various recycled blends that can be used are described.
[0085] Blend A1 Total C2 content 10-15% by weight, C2 (CF) content 8-12% by weight, C2 (SF) content 29-32% by weight, MFR 212-14g / 10min, tensile modulus 1200-1300MPa, impact strength (Charpy test 23℃) 5-6KJ / m 2 .
[0086] Blend A2 Total C2 content 6-7% by weight, C2 (CF) content 4-5% by weight, C2 (SF) content 29-30% by weight, MFR 221-28g / 10min, tensile modulus 1200-1300MPa, impact strength (Charpy test 23℃) 3-4KJ / m 2 .
[0087] Blend A3 Total C2 content 8-9% by weight, C2 (CF) content 4-5% by weight, C2 (SF) content 30-34% by weight, MFR 232-34g / 10min, tensile modulus 1300-1400MPa, impact strength (Charpy test 23℃) 5-6.5KJ / m 2 .
[0088] Blend A4 MFR2: 18-19g / 10min, tensile modulus 1200-1300MPa, impact strength (Charpy test 23℃) 5-6KJ / m 2 .
[0089] Blend A5 Total C2 content 9-11% by weight, C2 (CF) content 7-8% by weight, C2 (SF) content 32-33% by weight, MFR 224-25g / 10min, tensile modulus 1300-1400MPa, impact strength (Charpy test 23℃) 5-6KJ / m 2 .
[0090] Blend A6 Total C2 content 7-9% by weight, C2 (CF) content 5-7% by weight, C2 (SF) content 29-34% by weight, MFR 223-25g / 10min, tensile modulus 1100-1300MPa, impact strength (Charpy test 23℃) 4-5KJ / m 2 .
[0091] Blend A7 Total C2 content 7-9% by weight, C2 (CF) content 5-7.5% by weight, C2 (SF) content 27-33% by weight, MFR 215-17g / 10min, tensile modulus 1200-1300MPa, impact strength (Charpy test 23℃) 5-6KJ / m 2 .
[0092] Blend A8 Total C2 content 7-9% by weight, C2 (CF) content 4-6% by weight, C2 (SF) content 29-33% by weight, MFR 215-22g / 10min, tensile modulus 1200-1400MPa, impact strength (Charpy test 23℃) 4-7KJ / m 2 .
[0093] Heterophasic Propylene Copolymer The at least one heterophasic propylene copolymer may be used in an amount of 8 to 13 wt. %, preferably 9 to 11 wt. % (based on the total weight of the polymer composition).
[0094] In one embodiment, the at least one heterophasic propylene copolymer may be at least one reactor modified heterophasic propylene copolymer (HPC) having a melt flow rate MFR2 (measured according to ISO 1133 at 230°C, 2.16 kg) in the range of 10 to 25 g / 10 min, preferably 15 to 20 g / 10 min, more preferably 17 to 19 g / 10 min.
[0095] Heterophasic propylene copolymers (HPC) shall have a Charpy notched impact strength (NIS) of at least 25 kJ / m2 measured at 23°C according to ISO 179-1 eA. 2 , preferably at least 30 kJ / m 2 , more preferably at least 35 kJ / m 2 , for example 25 to 45 kJ / m 2 in the range of 30 to 40 kJ / m 2 range, e.g. 35 kJ / m 2 The heterophasic propylene copolymer (HPC) may have a flexural modulus, measured according to ISO 178, of at least 500 MPa, preferably at least 700 MPa, for example in the range of 500 to 1500 MPa, preferably in the range of 700 to 1000 MPa, for example 800 MPa.
[0096] Heterophasic propylene copolymers (HPC) are known in the art and are commercially available, for example, from Borealis AG.
[0097] In a further embodiment, the heterophasic propylene copolymer (HPC) may be aerated. Such aerated heterophasic propylene copolymers (HPC-AR) are known in the art and commercially available, for example from Borealis AG.
[0098] Elastomer The at least one elastomer may be used in an amount of 1.5 to 3.5% by weight, preferably 1.5 to 2.5% by weight, for example 2% by weight (based on the total weight of the polymer composition).
[0099] At least one elastomer is an ethylene / propylene copolymer with different C2 / C3 ratios (C2 / C3 or C3 / C2 elastomers), an ethylene / butene copolymer (C2 / C4 elastomer), an ethylene / octene copolymer (C2 / C8 elastomer), a grafted ethylene elastomer (such as an MAH-grafted ethylene elastomer), or a C2 / C3 and C2 / C4 block copolymer, in particular an ethylene-based 1-octene elastomer.
[0100] The elastomers preferably used are very low density ethylene-octene copolymers (EO-CoP) which have good flow and impact properties in blends with polypropylene and polyethylene. The ethylene-based 1-octene elastomers have a MFR (190°C, 2.16 kg) of 0.5-8 g / 10 min, a MFR of 850-860 kg / m 3 Such compounds are commercially available.
[0101] Glass fiber / coupling agent As mentioned above, the polyolefin composition according to the present invention contains glass fibers, in particular short glass fibers. Preferably, the glass fibers used in the fiber-reinforced composite have an average fiber length in the range of 2.0 to 10.0 mm, preferably in the range of 2.0 to 8.0 mm, even more preferably in the range of 2.0 to 6.0 mm, even more preferably in the range of 3.0 to 5.5 mm, even more preferably in the range of 3.5 to 5.0 mm.
[0102] More preferably, the short glass fibers used in the fiber reinforced composite have an average diameter of 5 to 20 μm, more preferably 8 to 18 μm, even more preferably 8 to 15 μm, even more preferably 10 to 15 μm, preferably 11 to 14 μm, preferably 12 to 14 μm, more preferably 12.3 to 13.7 μm, even more preferably 12.5 to 13.5 μm.
[0103] In a preferred embodiment, glass fibers having a fiber length of 3.0 to 5.0 mm (average 4.0 mm) and a fiber diameter of 12.3 to 13.7 μm (average 13 μm) are used. In another preferred embodiment, glass fibers having a fiber length of 3.5 to 5.5 mm (average 4.5 mm) and a fiber diameter of 12 to 14 μm (average 13 μm) are used.
[0104] As also mentioned above, the polyolefin composition according to the present invention comprises at least one coupling agent. The at least one coupling agent is a functionalized polypropylene, in particular a polypropylene functionalized with maleic anhydride (MAH). The amount of coupling agent in the polyolefin composition may be 1-2% by weight, for example 1% by weight or 1.25% by weight.
[0105] More specific embodiments of the polymer composition according to the present invention will be described below. In the first embodiment, a) 20-30% by weight (based on the total weight of the polymer composition) of at least one polypropylene homopolymer (PPH-1) having a melt flow rate MFR2 (230°C, 2.16 kg, measured according to ISO 1133) in the range of 10-30 g / 10 min, preferably 15-25 g / 10 min, more preferably 20 g / 10 min; b) a blend of recycled plastic materials comprising 30-40% by weight (based on the total weight of the polymer composition) of polypropylene and polyethylene in a ratio of 3:7 to 49.5:1, recovered from waste plastic materials originating from post-consumer and / or industrial waste; c) 8-12 wt. % (based on the total weight of the polymer composition) of at least one heterophasic propylene copolymer (HPC) having a melt flow rate MFR2 (230°C, 2.16 kg, measured according to ISO 1133) in the range of 10-25 g / 10 min, preferably 15-20 g / 10 min, more preferably 17-19 g / 10 min; d) 1-3 wt. % (based on the total weight of the polymer composition) of at least one ethylene-based 1-octene elastomer having a MFR2 (190°C, 2.16 kg) of 0.5-8 g / 10 min; e) 15 to 25% by weight (based on the total weight of the polymer composition) of glass fibers; and f) 1 to 1.5 wt. % (based on the total weight of the polymer composition) of at least one coupling agent, and optionally further additives; Here, all components are added so that the total always equals 100% by weight. A polyolefin composition is provided comprising:
[0106] Such a first polyolefin composition may have: - Fogging value of 1.3 to 1.5 (measured gravimetrically according to ISO 75201, method B); - a melt flow rate MFR2 (measured according to ISO 1133 at 230 ° C, 2.16 kg) in the range of 8 to 10 g / 10 min, preferably in the range of 8.5 to 9.5 g / 10 min; - a tensile modulus (ISO 527-2) of at least 4 GPa, preferably at least 4.5 GPa; - At least 6kJ / m 2 , preferably at least 6.5 kJ / m 2 , more preferably at least 7.0 kJ / m 2 Impact strength (Charpy 1eA +23℃).
[0107] In a second embodiment, a1) 10-15% by weight (based on the total weight of the polymer composition) of at least one polypropylene homopolymer (PPH-1) having a melt flow rate MFR2 (230°C, 2.16 kg, measured according to ISO 1133) in the range of 10-30 g / 10 min, preferably 15-25 g / 10 min, more preferably 20 g / 10 min; a2) 10-15% by weight (based on the total weight of the polymer composition) of at least one polypropylene homopolymer (PPH-3) having a melt flow rate MFR2 (230°C, 2.16 kg, measured according to ISO 1133) in the range of 100-150 g / 10 min, preferably 110-130 g / 10 min, more preferably 125 g / 10 min; b) a blend of recycled plastic materials comprising 30-40% by weight (based on the total weight of the polymer composition) of polypropylene and polyethylene in a ratio of 3:7 to 49.5:1, recovered from waste plastic materials originating from post-consumer and / or industrial waste; c) 8-12 wt. % (based on the total weight of the polymer composition) of at least one heterophasic propylene copolymer (HPC) having a melt flow rate MFR2 (230°C, 2.16 kg, measured according to ISO 1133) in the range of 10-25 g / 10 min, preferably 15-20 g / 10 min, more preferably 17-19 g / 10 min; d) 1-3 wt. % (based on the total weight of the polymer composition) of at least one ethylene-based 1-octene elastomer having a MFR (190° C., 2.16 kg) between 0.5 and 8 g / 10 min; e) 15 to 25% by weight (based on the total weight of the polymer composition) of glass fibers; and f) 1 to 1.5 wt. % (based on the total weight of the polymer composition) of at least one coupling agent, and optionally further additives; Including, Here, all components are added so that the total always equals 100% by weight. A polyolefin composition is provided comprising:
[0108] Such a second polyolefin composition may have the following: - Fogging value of 1.3 to 1.45 (measured gravimetrically according to ISO 75201, method B); - a melt flow rate MFR2 (230 ° C, 2.16 kg, measured according to ISO 1133) in the range of 10 to 15 g / 10 min, preferably in the range of 11 to 13 g / 10 min, for example 12 g / 10 min; - a tensile modulus (ISO 527-2) of at least 4 GPa, preferably at least 4.5 GPa; - At least 5.5kJ / m 2 , preferably at least 6.0 kJ / m 2 , more preferably at least 6.5 kJ / m 2 Impact strength (Charpy 1eA +23℃).
[0109] Additives In a further embodiment, the polyolefin composition may contain further additives. Examples of additives for use in the composition are pigments or dyes (e.g., carbon black), stabilizers (antioxidants), anti-acid and / or anti-UV agents, antistatic agents, nucleating agents and utilization agents (processing aids, etc.). Preferred additives are carbon black, at least one antioxidant and / or at least one UV stabilizer.
[0110] Generally, the amount of these additives is in the range of 0 to 5.0% by weight, preferably in the range of 0.01 to 3.0% by weight, more preferably 0.01 to 2.0% by weight, based on the weight of the total composition.
[0111] Examples of antioxidants commonly used in the art are sterically hindered phenols (also sold as Irganox 1010 FF (trademark) by BASF, such as CAS number 6683-19-8), phosphorus-based antioxidants (also sold as Hostanox PAR 24 (FF) (trademark) by Clariant, such as CAS number 31570-04-4, or Irgafos 168 (FF) (trademark) by BASF), sulfur-based antioxidants (sold as Irganox PS-802 FL (trademark) by BASF, such as CAS number 693-36-7), nitrogen-based antioxidants (such as 4,4'bis(1,1'-dimethylbenzyl)diphenylamine). Preferred antioxidants may be tris(2,4-di-t-butylphenyl)phosphite and / or octadecyl 3-(3',5'-di-t-butyl-4-hydroxyphenyl)propionate.
[0112] Antiacid agents are also commonly known in the art, such as calcium stearate, sodium stearate, zinc stearate, magnesium oxide and zinc oxide, synthetic hydrotalcites (e.g., SHT, CAS number 11097-59-9), lactates and lactylates, as well as calcium stearate (CAS number 1592-23-0) and zinc stearate (CAS number 557-05-1).
[0113] Common antiblocking agents include natural silicas such as diatomaceous earth (CAS No. 60676-86-0 (SuperfFloss™), CAS No. 60676-86-0 (SuperFloss E™) or CAS No. 60676-86-0 (Celite™). 499 (trademark); synthetic silica (e.g., CAS No. 7631-86-9, CAS No. 7631-86-9, CAS No. 7631-86-9, CAS No. 7631-86-9, CAS No. 7631-86-9, CAS No. 7631-86-9, CAS No. 112926-00-8, CAS No. 7631-86-9, or CAS No. 7631-86-9); silicates (e.g., aluminum silicate (kaolin) (CAS No. 1318-74-7), sodium aluminum silicate (CAS No. 1344-00-9), calcined kaolin (CAS No. 92704-41-1), aluminum silicate (CAS No. 1327-36-2), or calcium silicate (CAS No. 1344-95-2); synthetic zeolites (e.g., sodium calcium aluminosilicate hydrate (sodium calcium aluminosilicate hydrate, CAS number 1344-01-0, CAS number 1344-01-0), or sodium calcium aluminosilicate hydrate (CAS number 1344-01-0).
[0114] Anti-UV agents are, for example, bis(2,2,6,6-tetramethyl-4-piperidyl)-sebacate (CAS number 52829-07-9, Tinuvin 770); 2-hydroxy-4-n-octoxy-benzophenone (CAS number 1843-05-6, Chimassorb 81). Preferred UV stabilizers are mixtures of low and / or high molecular weight UV stabilizers, such as n-hexadecyl-3,5-di-t-butyl-4-hydroxybenzoate, 2,2,6,6-tetramethyl-4-piperidinol and higher fatty acids (mainly stearic acid) and / or poly((6-morpholino-s-triazine-2,4-diyl)(1,2,2,6,6-pentamethyl-4-piperidyl)imino)hexamethylene(1,2,2,6,6-pentamethyl-4-piperidyl)imino).
[0115] Sodium benzoate (CAS number 532-32-1); α-nucleating agents such as 1,3:2,4-bis(3,4-dimethylbenzylidene)sorbitol (CAS number 135861-56-2, Millad 3988). Suitable antistatic agents are, for example, glycerol esters (CAS number 97593-29-8) or ethoxylated amines (CAS numbers 71786-60-2 or 61791-31-9) or ethoxylated amides (CAS number 204-393-1). Usually, these additives are added in amounts of 100 to 2.000 ppm per individual component of the polymer.
[0116] It is understood that the present invention also refers to a process for producing a polyolefin composition as defined herein, said process comprising the following steps: - providing a mixture of at least one polypropylene homopolymer a); a blend of recycled materials b); at least one heterophasic propylene copolymer c); at least one elastomer d); glass fibers e) and at least one coupling agent in the required amount, - melting the mixture in an extruder; and - optionally pelletizing the polyolefin composition obtained.
[0117] For purposes of the present invention, mixing and melting can be accomplished using any suitable melting and mixing means known in the art.
[0118] However, the melting and mixing step is preferably carried out in a mixer and / or blender, a high or low shear mixer, a high speed blender, or a twin screw extruder. Most preferably, the melting and mixing step is carried out in a twin screw extruder, such as a co-rotating twin screw extruder. Such twin screw extruders are well known in the art, and the skilled person will adapt the melting and mixing conditions (e.g., melt temperature, screw speed, etc.) according to the process equipment.
[0119] The polyolefin compositions according to the present invention can be used in a wide range of applications, such as the manufacture of structural products, electrical appliances, automotive articles, pipes, films, geomembranes, roofing applications, pond liners, packaging, caps and closures. In addition, due to the sufficient tensile properties of the compositions according to the present invention, they can be used as films (having a thickness of 400 microns or less) or flexible foils (having a thickness of more than 400 microns), such as geomembranes for agriculture, roofing, and pond liners. Typically, the compositions described herein are used as the core layer of a multi-layer sheet (e.g., a three-layer geomembrane sheet), where the outer layers are made of various types of polyolefin materials. The most preferred application is in the automotive field. EXAMPLES
[0120] Experimental Section The following examples are included to demonstrate certain aspects and embodiments of the claimed invention. However, those of ordinary skill in the art should understand that the following descriptions are merely illustrative and should not be construed as limiting the invention in any way.
[0121] Test Method The following definitions of terms and determination methods apply to the above general description of the invention as well as to the following examples, unless otherwise defined.
[0122] a) Determination of the contents of isotactic polypropylene (iPP), polystyrene (PS), ethylene, PVC and polyamide-6 in the recycled blends
[0123] Sample preparation All calibration and analyte samples were prepared in a similar way on melt-pressed plates. Approximately 2-3 g of the analyte compound was melted at 190 °C. Subsequently, a pressure of 60-80 bar was applied for 20 seconds in a hydraulic heating press. The sample is then cooled in 40 seconds to room temperature in a cold press under the same pressure to control the morphology of the compound. The thickness of the plates was controlled by a metal calibrated frame plate of 2.5 cm x 2.5 cm and 100-200 μm thick (depending on the MFR from the sample), two plates were produced in parallel at the same moment and under the same conditions. The thickness of each plate was measured before any FTIR measurement, and all plates were 100-200 μm thick. All plates were pressed between two double-sided silicone release papers to control the plate surface and avoid any interference during the measurements. In case of powder samples or heterogeneous compounds, this pressing process was repeated three times to increase homogeneity by pressing and cutting the samples under the same conditions as above.
[0124] Spectrometer: A standard transmission type FTIR spectrometer, such as a Bruker Vertex 70 FTIR spectrometer, was used with the following settings: Spectral range: 4000~400cm -1 ; Aperture: 6mm; Spectral resolution: 2cm -1 ; · Background scan: 16, Spectral scan: 16; ·Interferogram zero filling factor: 32; ·Norton-Beer strong apodisation.
[0125] Spectra were recorded and analyzed using Bruker Opus software.
[0126] Calibration sample: Since FTIR is a secondary method, several calibration standards were compounded to cover the analytical range of interest, typically: · 0.2wt% to 2.5wt% for PA; · For PS, 0.1% to 5% by weight; · For PET, 0.2% to 2.5% by weight; For PVC, 0.1% to 4% by weight.
[0127] The following commercially available materials were used in the compounds: Borealis HC600TF (as iPP), Borealis FB3450 (as HDPE), and the target polymers (RAMAPET N1S (Indorama Polymer) for PET, Ultramid® B36LN (BASF) for Polyamide 6, Styrolution PS 486N (Ineos) for high impact polystyrene (HIPS), and PVC Inovyn PVC263B (in powder form).
[0128] All compounds were prepared on a small scale in a Haake compounder at temperatures below 265° C. and for less than 10 minutes to avoid decomposition. Additional antioxidants such as Irgafos 168 (3000 ppm) were added to minimize decomposition.
[0129] Calibration: The FTIR calibration principle was the same for all components: the intensity of a particular FTIR band divided by the plate thickness was calculated for the same plate. 1 H or 13 C correlated with the amounts of the components determined by solution-state NMR.
[0130] Each specific FTIR absorption band was selected because it increases in intensity with the amount of component concentration and is resolved from the remaining peaks, regardless of the composition of the calibration standards and the actual sample.
[0131] This methodology is described in the publication by Signoret et al.: "Changes in plastic spectra in the MIR and potential impacts on identification for recycling", Resources, conservation and Recycling journal, 2020, volume 161, article 104980.
[0132] The wavelengths for each calibration band are: For PA, 3300 cm -1 ; For PS, 1601cm -1 ; For PET, 1410cm -1 ; For PVC, 615 cm -1 ; For iPP, 1167 cm -1 It is.
[0133] For each polymer component i, a linear calibration (based on the linearity of the Beer-Lambert law) was constructed. A typical linear correlation used for such a calibration is shown below:
[0134]
number
[0135] where x i is the fraction (wt%) of polymer component i. E i is the absorbance (i.e., in absorbance units) of the specific bands associated with polymer component i. These specific bands are: 3300 cm for PA; -1 , 1601cm for PS -1 , 1410 cm for PET -1 , 615cm for PVC -1 , 1167 cm for iPP -1 It is. d is the thickness of the sample plate. A i and B. iare the two correlation coefficients determined for each calibration curve.
[0136] No specific isolated band was found for the C2-rich fraction, so the C2-rich fraction was indirectly estimated:
[0137]
number
[0138] The EVA, chalk and talc contents are estimated "semi-quantitatively". This therefore makes the C2 rich content "semi-quantitative".
[0139] For each calibration standard, wherever possible, the amount of each component is 1 H or 13 C was determined by solution-state NMR of either (except for PA). The NMR measurements were performed on the exact same FTIR plate used to construct the FTIR calibration curve.
[0140] Calibration standards were prepared by mixing iPP and HDPE to construct a calibration curve. The thickness of the films of the calibration standards was 300 μm. For the quantification of the contents of iPP, PS and PA6 in the samples, quantitative IR spectra were recorded in the solid state using a Bruker Vertex 70 FTIR spectrometer. The spectra were recorded on square films of 25 × 25 mm and 50–100 μm thick, prepared by compression molding at 190 °C and 4–6 mPa. Standard transmission FTIR spectroscopy was performed at 4000–400 cm. -1 Spectral range, 6mm aperture, 2cm -1 The measurements were performed with a spectral resolution of 100 kHz, 16 background scans, 16 spectral scans, an interferogram zero filling factor of 32, and Norton-Beer strong apodization.
[0141] About iPP, 1167cm -1The absorption of the bands at 100 nm was measured and the iPP content was quantified according to a calibration curve (absorption / thickness (cm) vs. iPP content (wt%)).
[0142] 1601cm -1 (PS) and 3300cm -1 The absorption of the bands in (PA6) was measured and the PS and PA6 contents were quantified according to a calibration curve (absorption / thickness (cm) vs. PS and PA content (wt%)). The ethylene content was obtained by subtracting the iPP, PS and PA6 contents from 100. The analysis was performed in duplicate.
[0143] b) The amount of talc and chalk in the recycled blend was measured by thermogravimetric analysis (TGA); the experiments were carried out using a Perkin Elmer TGA 8000. Approximately 10-20 mg of material was placed in a platinum pan. The temperature was equilibrated at 50°C for 10 minutes and then increased to 950°C under nitrogen at a heating rate of 20°C / min. The weight loss (WCO2) between approximately 550°C and 700°C was attributed to CO2 evolved from CaCO3 and therefore the chalk content was estimated as follows: Chalk content = 100 / 44 x WCO2
[0144] The temperature was then reduced to 300°C at a cooling rate of 20°C / min. The gas was then switched to oxygen and the temperature was increased again to 900°C. The weight loss during this process was assigned to carbon black (Wcb). Knowing the carbon black and chalk contents, the ash content excluding chalk and carbon black was calculated as follows: Ash content = (ash content remaining) -56 / 44 x WCO2 - Wcb
[0145] Here, the ash residue is the weight percent measured at 900° C. in the first step carried out under nitrogen. The ash content is assumed to be the same as the talc content of the investigated recycles.
[0146] c) Amount of paper and wood in the recycled blend Paper and wood were determined by conventional laboratory methods including milling, flotation, microscopy and thermogravimetric analysis (TGA) or flotation techniques (dissolving the polymer and determining the paper and wood content gravimetrically).
[0147] d) The amount of metals in the recycled blend was determined by x-ray fluorescence (XRF).
[0148] e) The amount of limonene in the recycled blend was determined by solid phase microextraction (HS-SPME-GC-MS). Further details regarding specific samples are provided below.
[0149] f) The amount of total fatty acids in the recycle blend was determined by solid phase microextraction (HS-SPME-GC-MS). Further details regarding specific samples are provided below.
[0150] g) Xylene Cold Solubility (XCS) in the recycle blend is measured at 25°C according to ISO 16152; First Edition; 2005-07-01.
[0151] h) Crystallography of recycled blends Crystallization and soluble fractionation The crystalline (CF) and soluble (SF) fractions of polypropylene (PP) compositions, as well as the comonomer content and intrinsic viscosity of each fraction, were analyzed with a CRYSTEX QC from Polymer Char (Valencia, Spain). The crystalline and amorphous fractions were separated by temperature cycling: dissolution at 160°C, crystallization at 40°C, and redissolution in 1,2,4-trichlorobenzene (1,2,4-TCB) at 160°C.
[0152] Quantification of SF and CF of the parent EP copolymer and its soluble and crystalline fractions as well as determination of the ethylene content (C2) are achieved by means of an infrared detector (IR4) and an on-line 2-capillary viscometer used for the determination of intrinsic viscosity (iV). The IR4 detector is a multi-wavelength detector that detects infrared absorbance in two different bands (CH3 and CH2) to measure the concentration and ethylene content in ethylene-propylene copolymers. The IR4 detector detects ethylene content between 2% and 69% by mass ( 13 The calibration is performed with eight EP copolymers known in the range of 100 to 150 nm (determined by C-NMR spectroscopy) and various concentrations between 2 and 13 mg / ml of each EP copolymer used for the calibration.
[0153] The amounts of soluble fraction (SF) and crystalline fraction (CF) are correlated through XS calibration to the "cold xylene soluble" (XCS) and "cold xylene insoluble" (XCI) fractions, respectively, determined according to standard gravimetric methods according to ISO 16152. The XS calibration is achieved by testing a range of EP copolymers with XS contents ranging from 2 to 31% by mass.
[0154] The intrinsic viscosities (iV) of the parent EP copolymer, its soluble and crystalline fractions are measured using an online two-capillary viscometer and correlated with the corresponding iV measured by the standard method in decalin according to ISO 1628. Calibration was achieved with various EP PP copolymers with iV=2-4 dL / g.
[0155] A sample of the PP composition to be analyzed is weighed out at a concentration of 10 mg / ml to 20 mg / ml. After automatic filling of a vial with 1,2,4-TCB containing 250 mg / l of 2,6-tert-butyl-4-methylphenol (BHT) as an antioxidant, the sample is dissolved at 160 °C with constant stirring at 800 rpm until completely dissolved, typically for 60 min.
[0156] A certain amount of sample solution is injected into a column packed with an inert carrier, where the sample crystallizes and the soluble fraction is separated from the crystalline part. This process is repeated twice. In the first injection, the entire sample is measured at high temperature to determine the iV [dl / g] and C2 [mass%] of the PP composition. In the second injection, the soluble fraction (low temperature) and the crystalline fraction (high temperature) are measured following the crystallization cycle (mass% SF, mass% C2, iV). EP means ethylene propylene copolymer. PP means polypropylene.
[0157] i) Regio-defects: Quantification of microstructure by NMR spectroscopy Quantitative nuclear magnetic resonance (NMR) spectroscopy was further used to quantify the comonomer content and comonomer sequence distribution of the polymers. 13 C{ 1 H}NMR spectra were obtained in solution using a Bruker Advance III 400 NMR spectrometer. 1 H and 13 C and 400.15 MHz and 100.62 MHz, respectively. All spectra were 13 Temperatures were recorded at 125 °C using a 10 mm extended temperature probe head optimized for C and nitrogen gas for all air pressures. Approximately 200 mg of material was dissolved in 3 ml of 1,2-tetrachloroethane-d2 (TCE-d2) along with chromium(III)-acetylacetonate (Cr(acac)3) to obtain a 65 mM solution of the relaxation agent in the solvent (Singh, G., Kothari, A., Gupta, V., Polymer Testing 28 5(2009),475). After initial sample preparation in a heat block to ensure a homogenous solution, the NMR tube was heated in a rotating oven for at least 1 hour. Once inserted in the magnet, the tube was spun at 10 Hz. This setup was chosen primarily for the high resolution and quantitative nature required for accurate ethylene content quantification. Standard single-pulse excitation was employed without NOE, using an optimized tip angle, a 1 second recycle delay, and a binary WALTZ16 decoupling scheme (Zhou, Z., Kuemmerle, R., Qiu, X., Redwine, D., Cong, R., Taha, A., Baugh, D., Winniford, B., J. Mag. Reson. 187 (2007) 225; Busico, V., Carbonniere, P., Cipullo, R., Pellecchia, R., Severn, J., Talarico, G., Macromol. Rapid Commun. 2007, 28, 1128). A total of 6144 (6k) transients were acquired per spectrum.
[0158] quantitative13 C{ 1 H}NMR spectra were processed, integrated, and relevant quantitative properties were determined from the integrals using a proprietary computer program. All chemical shifts were indirectly referenced to the central methylene group of the ethylene block (EEE) at 30.00 ppm using the chemical shift of the solvent. This approach allowed for equivalent referencing even in the absence of this structural unit. Characteristic signals corresponding to ethylene incorporation were observed (Cheng, HN, Macromolecules 17 (1984), 1950).
[0159] 2,1 Because characteristic signals corresponding to erythro regio-defects were observed, it was necessary to correct for the influence of regio-defects on the determined properties. No characteristic signals corresponding to other types of regio-defects were observed (described in L. Resconi, L. Cavallo, A. Fait, F. Piemontesi, Chem. Rev. 2000, 100(4), 1253, in Cheng, HN, Macromolecules 1984, 17, 1950, and in WJ. Wang and S. Zhu, Macromolecules 2000, 33 1157).
[0160] The comonomer fraction is 13 C{ 1 Quantification was performed using the method of Wang et al. (Wang, WJ., Zhu, S., Macromolecules 33 (2000), 1157) by integrating multiple signals over the entire spectral region of the {H} spectrum. This method was chosen for its robust nature and its ability to take into account the presence of regio-defects when necessary. The integration region was slightly adjusted to increase applicability over the entire range of comonomer contents encountered.
[0161] For systems where only isolated ethylene in the PPEPP sequence was observed, the method of Wang et al. was modified to reduce the effect of non-zero integrals of sites known to be absent. This approach reduced the overestimation of ethylene content in such systems, accomplished by reducing the number of sites used to determine absolute ethylene content as follows: E=0.5(Sββ+Sβγ+Sβδ+0.5(Sαβ+Sαγ))
[0162] Using this set of sites, the corresponding integral equation becomes: E = 0.5(I H +I G +0.5(I C +I D )) The same notation used in the paper by Wang et al. (Wang, WJ., Zhu, S., Macromolecules 33 (2000), 1157) is used. The formula used for absolute propylene content was unchanged.
[0163] The mole % comonomer incorporation was calculated from the following mole fractions: E[mol%]=100*fE
[0164] Weight percent comonomer incorporation was calculated from the following mole fractions: E[wt%]=100*(fE*28.06) / ((fE*28.06)+((1-fE)*42.08))
[0165] Comonomer sequence distribution at the triad level was determined using the analytical method of Kakugo et al. (Kakugo, M., Naito, Y., Mizunuma, K., Miyatake, T. Macromolecules 15 (1982) 1150). This method was chosen for its robust nature, and the integral region was slightly adjusted to increase applicability to a wider range of comonomer contents.
[0166] j) Melt flow rate was measured as indicated at 230°C or 190°C under a load of 2.16 kg (MFR2). Melt flow rate is the amount of polymer (g) that an ISO 1133 compliant testing apparatus will extrude in 10 minutes at a temperature of 230°C (or 190°C) under a load of 2.16 kg.
[0167] k) Tensile modulus, tensile strength, tensile strain at break, tensile strain at tensile strength, tensile stress at break, flexural modulus Measurements were performed after a conditioning period of 96 hours (23° C., 50% relative humidity) of the sample pieces.
[0168] The tensile modulus was measured according to ISO 527-2 (crosshead speed = 1 mm / min, 23°C) using injection moulded sample specimens (dogbone shape, 4 mm thick) as described in EN ISO 1873-2.
[0169] Tensile strength and tensile strain at break were measured according to ISO 527-2 (crosshead speed = 50 mm / min, 23°C) using injection moulded sample specimens (dogbone shape, 4 mm thick) as described in EN ISO 1873-2.
[0170] The tensile strain at the tensile strength was measured using injection-molded sample specimens (dogbone shape, 4 mm thick) as described in EN ISO 1873-2 at an elongation rate of 50 mm / min according to ISO 527-2 until the sample specimen broke.
[0171] Tensile stress at break was measured according to ISO 527-2 (crosshead speed = 50 mm / min) on samples prepared from compressed plaques with a sample thickness of 4 mm.
[0172] The flexural modulus was measured according to the ISO 178 standard.
[0173] i) Impact strength was determined as Charpy impact strength on injection-molded sample pieces of 80 x 10 x 4 mm prepared according to EN ISO 1873-2 at +23°C (notched) according to ISO 179-1 / 1eA or at +23°C (unnotched) according to ISO 179-1 / 1eU. According to this standard, the samples are tested after 96 hours.
[0174] m) Fogging: Gravimetric fogging is measured according to ISO 75201 method B using sample pieces (diameter 80 mm ± 1 mm, thickness 2 mm) cut from injection molded plates. Fogging refers to the evaporation of volatile substances in automotive interior trim materials. This method evaluates the volatility of organic components by gravimetric measurement. The samples were dried in a desiccator with silica gel at room temperature for 24 hours. The test was performed at 100 °C for 16 hours. The beaker is sealed with tarred aluminum foil (diameter 103 mm, thickness 0.03 mm), a glass plate, and a cooling plate (21 °C). After the test time (16 hours ± 10 minutes at 100 °C ± 0.3 °C), the glass plate is removed, the aluminum foil is removed, and the silica gel is used as a discant, dried in a desiccator at room temperature for 3.5 to 4.0 hours, and weighed back. The gravimetric fogging value "G" (mg) is calculated by the following formula: G = weight of aluminum foil after fogging test - tare weight of aluminum foil, unit mg G sample = average of two aluminum foils used for two specimens of each sample
[0175] Table 1 summarizes some examples (Comparative Examples - CE; Inventive Examples - IE).
[0176] Different blends of recycled materials were used, characterized by the following properties:
[0177] Blend A1: Total C2 content 10-15% by weight, C2 (CF) content 8-12% by weight, C2 (SF) content 29-32% by weight, MFR 212-14g / 10min, tensile modulus 1200-1300MPa, impact strength (Charpy test 23℃) 5-6KJ / m 2 .
[0178] Blend A2: Total C2 content 6-7% by weight, C2 (CF) content 4-5% by weight, C2 (SF) content 29-30% by weight, MFR 221-28g / 10min, tensile modulus 1200-1300MPa, impact strength (Charpy test 23℃) 3-4KJ / m 2 .
[0179] Blend A5: Total C2 content 9-11% by weight, C2 (CF) content 7-8% by weight, C2 (SF) content 32-33% by weight, MFR 224-25g / 10min, tensile modulus 1300-1400MPa, impact strength (Charpy test 23℃) 5-6KJ / m 2 ;
[0180] Blend A8: Total C2 content 7-9% by weight, C2 (CF) content 4-6% by weight, C2 (SF) content 29-33% by weight, MFR 215-22g / 10min, tensile modulus 1200-1400MPa, impact strength (Charpy test 23℃) 4-7KJ / m 2 ;
[0181] The reactor modified heterophasic propylene copolymer (HPC) has a melt flow rate MFR2 (230°C, 2.16 kg, measured according to ISO 1133) of 17-19 g / 10 min.
[0182] Table 1 refers to a polyolefin composition comprising: - Comparative Example (CE1): A blend of one first polypropylene homopolymer (PPH-1 with MFR2 of 20 g / 10 min), a second polypropylene homopolymer (PPH-3 with MFR2 of 125 g / 10 min), recycled material (Blend A1) and at least one heterophasic propylene copolymer (HPC); Comparative Example (CE2): One blend of one polypropylene homopolymer (PPH-3 with MFR2 of 125 g / 10 min), recycled material (Blend A1) and at least one heterophasic propylene copolymer (HPC). - Comparative Example (CE3): one blend of a first polypropylene homopolymer (PPH-1 with MFR2 of 20 g / 10 min) and a second polypropylene homopolymer (PPH-3 with MFR2 of 125 g / 10 min); one blend of recycled material (Blend A1); - inventive example (IE1): one first polypropylene homopolymer (PPH-1 with MFR2 of 20 g / 10 min) and one second polypropylene homopolymer (PPH-3 with MFR2 of 125 g / 10 min); a blend of recycled materials (blend A2), one blend of at least one heterophasic propylene copolymer (HPC) and at least one ethylene-octene copolymer (EO-CoP); - inventive example (IE2): one first polypropylene homopolymer (PPH-1 with MFR2 of 20 g / 10 min); one blend of recycled material (blend A2), at least one heterophasic propylene copolymer (HPC) and at least one ethylene-octene copolymer (EO-CoP); - inventive example (IE3): one first polypropylene homopolymer (PPH-1 with MFR2 of 20 g / 10 min); one blend of recycled material (blend A2), at least one heterophasic propylene copolymer (HPC) and at least one ethylene-octene copolymer (EO-CoP); - inventive example (IE4): one first polypropylene homopolymer (PPH-1 with MFR2 of 20 g / 10 min); one blend of recycled material (blend A2), at least one gas-containing heterophasic propylene copolymer (HPC-AR) and at least one ethylene-octene copolymer (EO-CoP); - inventive example (IE5): one first polypropylene homopolymer (PPH-1 with MFR2 of 20 g / 10 min); one blend of recycled material (blend A5), at least one heterophasic propylene copolymer (HPC) and at least one ethylene-octene copolymer (EO-CoP); - inventive example (IE6): one first polypropylene homopolymer (PPH-4 with MFR2 of 75 g / 10 min); one blend of recycled material (blend A2), at least one heterophasic propylene copolymer (HPC) and at least one ethylene-octene copolymer (EO-CoP), - inventive example (IE7a): one first polypropylene homopolymer (PPH-1 with MFR2 of 20 g / 10 min); a blend of recycled materials (blend A8), one blend of at least one heterophasic propylene copolymer (HPC) and at least one ethylene-octene copolymer (EO-CoP), - Inventive example (IE7b): one first polypropylene homopolymer (PPH-1 with MFR2 of 20 g / 10 min); one blend of recycled material (blend A8), at least one heterophasic propylene copolymer (HPC) and at least one ethylene-octene copolymer (EO-CoP).
[0183] Glass fibers can be obtained from one of the following sources: OC (Owens Corning), PPG / NEG, Johns Manville, 3B, Jushi, Taiwan Glass, Camelyaf, CPIC, Taishan, Glass fibers 1.2 (average length 4 mm, average diameter 13 μm) and 4.1 (average length 4.5 mm, average diameter 13 μm) are used.
[0184] The following additives were used: antioxidants: AO1 (Irganox 1010 (FF)), AO2 (Irganox B 225 (FF)), AO3 (Irganox PS-802 FL); black pigment (Plasblak PE6121, available from Cabot); Dosing agent: HC001A-B1, PP homopolymer power; Coupling agent: AP 1.5, polypropylene highly functionalized with maleic anhydride.
[0185] As can be seen in Table 1, the fogging values (IE1 to IE6) of the polyolefin compositions according to the invention are in each case lower than the fogging values of the comparative examples.
[0186] At the same time, the physical properties of the polyolefin compositions according to the present invention, such as melt flow rate, tensile modulus and Charpy impact strength, are within the same range as the comparative examples.
[0187] [Table 1]
Claims
1. a) 20 to 30 wt. % (based on the total weight of the polyolefin composition) of at least one polypropylene homopolymer; b) a blend of recycled plastic materials comprising 10-45% by weight (based on the total weight of the polyolefin composition) of polypropylene and polyethylene in a ratio of 3:7 to 49.5:1, recovered from waste plastic materials originating from post-consumer and / or post-industrial waste; c) 7 to 15 wt. % (based on the total weight of the polyolefin composition) of at least one heterophasic polypropylene copolymer; d) 1 to 4 weight percent (based on the total weight of the polyolefin composition) of at least one elastomer; e) 15 to 25 wt. % (based on the total weight of the polyolefin composition) of at least one glass fiber; and f) 0.5 to 2.5 wt. % (based on the total weight of the polyolefin composition) of at least one coupling agent and, optionally, further additives; Including, A polyolefin composition, wherein all components are added so that the total always equals 100% by weight, The polyolefin composition is characterized by: - Fogging value of 0.5 to 2.00 (measured gravimetrically according to ISO 75201, method B).
2. 2. The polyolefin composition of claim 1, characterized by a fogging value (measured gravimetrically according to ISO 75201, method B) of 0.75 to 1.
8.
3. Melt flow rate (MFR) of at least 7 g / 10 min 2 2. The polyolefin composition of claim 1, characterized by a modulus of elasticity of 1.0 g / mol / L (measured according to ISO 1133 at 230° C., 2.16 kg).
4. 2. The polyolefin composition of claim 1, characterized by a tensile modulus (ISO 527-2) of at least 3.5 GPa.
5. 2. The polyolefin composition of claim 1, characterized by a flexural modulus (ISO 178) of at least 3.5 GPa.
6. 2. The polyolefin composition of claim 1, characterized by an impact strength (ISO 179-1, Charpy 1eA +23° C.) of at least 5.0 kJ / m 2 .
7. 2. The polyolefin composition of claim 1, characterized in that the polypropylene homopolymer a) is selected from the group consisting of: - Melt flow rate MFR in the range of 10 to 30 g / 10 min 2 (230° C., 2.16 kg, measured according to ISO 1133); - Melt flow rate MFR in the range of 60 to 100 g / 10 min 2 (230° C., 2.16 kg, measured according to ISO 1133); - Melt flow rate MFR in the range of 100 to 150 g / 10 min 2 (230° C., 2.16 kg, measured according to ISO 1133); - Melt flow rate MFR in the range of 50 to 100 g / 10 min 2 (230° C., 2.16 kg, measured according to ISO 1133).
8. 20-40 wt. % (based on the total weight of the polyolefin composition) of polypropylene and polyethylene, with a melt flow rate MFR in the range of 5-100 g / 10 min. 2 2. The polyolefin composition according to claim 1, characterized in that it comprises a blend b) of recycled plastic materials having a viscosity of 100 MPa (measured according to ISO 1133 at 230° C., 2.16 kg).
9. 2. The polyolefin composition of claim 1, characterized in that the at least one heterophasic propylene copolymer is: at least one reactor heterophasic propylene copolymer (HPC) c) having a melt flow rate MFR in the range of 10 to 25 g / 10 min 2 (230° C., 2.16 kg, measured in accordance with ISO 1133).
10. 2. The polyolefin composition according to claim 1, characterized in that the at least one elastomer d) is an ethylene / propylene copolymer with different C2 / C3 ratios (C2 / C3 or C3 / C2 elastomers), an ethylene / butene copolymer (C2 / C4 elastomer), an ethylene / octene copolymer (C2 / C8 elastomer), a grafted ethylene elastomer, or a C2 / C3 and C2 / C4 block copolymer.
11. 2. The polyolefin composition of claim 1, wherein the glass fibers e) have an average length in the range of 2.0 to 10.0 mm and an average diameter of 5 to 20 μm.
12. 2. The polyolefin composition according to claim 1, characterized in that at least one coupling agent f) is a functionalized polypropylene.
13. Use of the polyolefin composition according to any one of claims 1 to 12 in the manufacture of construction products, household appliances, automotive articles.
14. An article comprising the polyolefin composition according to any one of claims 1 to 12.
15. A process for preparing the polyolefin composition according to any one of claims 1 to 12, comprising the steps of: - providing a mixture of at least one polypropylene homopolymer a); a blend of recycled materials b); at least one heterophasic propylene copolymer c); at least one elastomer d); glass fibres e) and at least one coupling agent. - melting the mixture in an extruder; and - Optionally, pelletizing the resulting polyolefin composition.
Citation Information
Patent Citations
Composition comprising two or more kinds of resins and glass long-fibers
EP2845876A1
Regeneration and utilization of scrap of molded article made of polyolefin resin
JP1995068551A
Colorant composition for polypropylene
JP2000129192A
Resin composition used for vehicle interior by using crushed material of vehicle bumper mingled with insoluble substance as raw material and molded article of the same
JP2005139421A
Irradiated and Oxidized Olefin Polymer Coupling Agent
JP2006508213A